Favorable epistasis in ancestral diterpene synthases promoted convergent evolution of a resin acid precursor in conifers - Andrew J. O’Donnell; Preston J. Pellatz; Caroline S. Nichols; Jonathan Gershenzon; Reuben J. Peters; Axel Schmidt (Proceedings of the National Academy of Sciences, 2025)
A long-standing question in biology is what makes evolution more or less repeatable. Although evolution seems repeatable when observing convergent phenotypic outcomes, each episode of convergence could have been contingent on an idiosyncratic history that is not expected to repeat. Overlooking events that preceded convergent episodes therefore risks overestimating repeatability. Here, we demonstrate using resurrected ancestral proteins that the evolution of a characteristic diterpene resin acid precursor, isopimaradiene, became especially repeatable in conifers following genetic divergence that simultaneously changed the effects of phenotype-altering substitutions in diterpene synthase enzymes. We found that millions of years of epistatic change prior to three genus-level episodes of convergent isopimaradiene formation led to ancestral diterpene synthases in the family Pinaceae that served as suitable starting points for evolving identical products. However, enzymes predating the Pinaceae formed different diterpenes when the same substitutions were introduced as mutations, indicating that critical alterations in the effects of substitution occurred after the origin of this plant family. Because these alterations occurred prior to the evolution of isopimaradiene, the convergence appears dependent on a history that is less likely to repeat. Our work shows how contingency can lead to repeatable evolution of a trait in related present-day plant lineages.